HUBUNGAN TERJADINYA ANEMIA DEFISIENSI ZAT BESI PADA IBU HAMIL DI PUSAT KESEHATAN MASYARAKAT (PKM) KASSI-KASSI MAKASSAR - Hasbullah, Ayu Ameliyah; Patiung, Adeviliani; Putra, Bayu Pratama (Siddiq Institute, 2023)
Anemia is a condition where hemoglobin levels decrease which causes the capacity and carrying capacity of oxygen for the body to be reduced. Iron deficiency anemia during pregnancy is a condition in which pregnant women experience iron deficiency arising from mother-fetal iron transfer, which is often exacerbated by a decrease in maternal iron reserves, with hemoglobin levels below 11 grams in the first and third trimesters or 10.5 grams in the second trimester. The purpose of this study was to determine the factors that are associated with the occurrence of iron deficiency anemia in pregnant women who visit ANC at PKM Kassi-Kassi Makassar. The method in this study is observational analytic with case control design and data analysis including univariate and bivariate data using the chi square test. This study was conducted on 72 samples of pregnant women who visited ANC at PKM Kassi-Kassi Makassar. The results of this study showed that the parity variable was obtained in pregnant women with a risk parity of 37 (51.4%) and in non-risky parity of 35 (48.6%) with a p-value of 0.018. Adherence to taking iron tablets (Fe) in non-compliant pregnant women as much as 44 (61.1%) and pregnant women who obeyed as much as 28 (38.9) with a p-value of 0.007. The level of education for pregnant women with basic education is elementary and junior high school education as much as 16 (22.2%) and pregnant women with the upper education level is high school and college 56 (77.8%) with a p-value of 0.155. Chronic Energy Deficiency (KEK) status in pregnant women with KEK status is at risk as much as 15 (20.8%) and pregnant women with KEK status is not at risk as much as 57 (79.2%) with a p-value of 0.018. The conclusion of this study is that there is a significant relationship between parity, adherence to taking Iron tablets and KEK status with the occurrence of iron deficiency anemia in pregnant women who visit ANC at PKM Kassi-Kassi Makassar.